Influences of polymer modifiers on Porous Hot Asphalt Mixture Property and Durability - Mohammed Q. Ali; Ganjeena J. Khoshanw (Polytechnic Journal)
Fundamentally, sustainability and cost-effectiveness in infrastructure development have received widespread attention. Permeable pavement is such a concept that it is sustainable in the field of transportation and is being tested. Fully permeable pavement is a modern design method in which each layer is porous and can store water, avoiding the impact of stormwater on the pavement to avoid stormwater, skidding, floods, and water splash on the road and parking area which decrease safety rate. Porous asphalt (PA) is an asphalt mixture with a little or no fine aggregate. Due to open structures and advantages are used as a drainage layer in highway pavements in reducing noise and decreasing safety hazards during rainfall. Besides, it reduces splash and spray effects and thus increases the visibility. The main aim of this study is to analyze the influence of two asphalt modifier types: Styrene butadiene styrene (SBS) and propylene modifier polypropylene (PP), on porous hot asphalt mixture performance. The PA evaluation influence findings are based on permeability, durability, and Marshall stability-flow for hot asphalt mixture. The test results emphasize the modifier usage in reducing the abrasion loss and increasing the stability with enhancing the durability of PA. PA mixture binder prepared with 4% SBS and 4% PP modifier was the most polymer binder in modifying the abrasion resistance and stability of mixture in pavements.